2019
DOI: 10.2355/isijinternational.isijint-2018-591
|View full text |Cite
|
Sign up to set email alerts
|

Emissions and Removal of Gaseous Pollutants from the Top-gas of a Blast Furnace

Abstract: The emissions of a blast furnace and the separation efficiency of the top-gas scrubber were investigated for the gaseous components HCl, H 2 S, SO 2 , COS, CS 2 , CH 3 SH, HCN and NH 3. The clean gas emission of sulphur was dominated by COS which accounted for about 85% of the total sulphur emissions. From the hydrogen halides only HCl was present above the detection limit and the concentrations of NH 3 and HCN were also low. The average separation efficiency for HCl, SO 2 and NH 3 was 96%, 81% and 46%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The analysis of the bottled real gases showed that the samples taken after the gas cleaning station and the gasometers are composed like typical average values in the steel industry [4] (Table 2). In addition, the following catalyst poisons were detected in the blast furnace gas [24,25]: carbon disulphide (CS 2 ) with a very small amount of 0.26 mg/Nm 3 . COS stabilised at 110 mg/Nm 3 , and the SO 2 content was evaluated with 2.2 mg/Nm 3 .…”
Section: Analysis Of Bottled Real Gasesmentioning
confidence: 99%
“…The analysis of the bottled real gases showed that the samples taken after the gas cleaning station and the gasometers are composed like typical average values in the steel industry [4] (Table 2). In addition, the following catalyst poisons were detected in the blast furnace gas [24,25]: carbon disulphide (CS 2 ) with a very small amount of 0.26 mg/Nm 3 . COS stabilised at 110 mg/Nm 3 , and the SO 2 content was evaluated with 2.2 mg/Nm 3 .…”
Section: Analysis Of Bottled Real Gasesmentioning
confidence: 99%
“…To achieve the catalytic removal of the COS gas from blast furnace gas by hydrolysis, it is necessary to obtain hydrolysis catalysts with excellent performance. 5,6 Nanocomposites with hollow spheres often have the advantages of a large specific surface area, tunable material size and stable properties, making them one of the most promising materials for hydrolysis catalysis. 7,8 There is an urgent need to prepare a nanoscale hollow sphere hydrolysis catalyst with low catalytic energy consumption, long catalytic lifetime and high conversion COS efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The main components of blast furnace gas are N 2 , CO 2 , CO, C m H n , H 2 , and their contents are 56~63%, 16~22%, 18~24%, 2~4%, 0.5~2.5%, respectively. In addition, blast furnace gas also contains hydrogen chloride (HCl), carbonyl sulfur (COS), hydrogen sulfide (H 2 S), NO x , furnace dust and water vapor, etc [7][8][9] . Zhang analyzed the condensate of blast furnace gas after dry dust removal in a steel plant and found that the pH value of condensate medium in blast furnace gas pipe network was between 1 and 2, belonging to strong acid solution 10) .…”
Section: Introductionmentioning
confidence: 99%